Identification of a secreted superoxide dismutase (SOD) from Nocardia seriolae which induces apoptosis in fathead minnow (FHM) cells. Issue 1 (21st September 2020) - Hou, Suying; Wang, Wenji; Chen, Guoquan; Xia, Liqun; Wang, Zhiwen; Lu, Yishan
Abstract: Fish nocardiosis is a chronic systemic granulomatous disease, and Nocardia seriolae is the main pathogen. The pathogenesis and virulence factors of N. seriolae are not fully understood. Secreted superoxide dismutase (SOD) may be a virulence factor found by a comparative bioinformatics analysis of the whole genome sequence of N. seriolae and the virulence factor database (VFDB). In order to determine the subcellular localization and study the preliminary function of SOD from N. seriolae (NsSOD), gene cloning, secreted protein identification, subcellular localization in fish cells, and apoptosis detection of NsSOD were carried out in this study. Subcellular localization research revealed that NsSOD‐GFP fusion proteins were evenly distributed in the cytoplasm. Furthermore, apoptotic bodies were observed in the transfected FHM cells by the overexpression of protein NsSOD. Then, assays of mitochondrial membrane potential (ΔΨm) value, caspase‐3 activity and apoptosis‐related genes (Bax, Bid, Bad and Bcl‐2) mRNA expression were conducted. The results showed that ΔΨm was decreased, and caspase‐3 was significantly activated. The mRNA expression of the Bad gene showed significant up‐regulated expression at 24 h.p.t., while Bid and Bax genes showed significant up‐regulated expression at 72 and 96 h.p.t. and anti‐apoptotic gene (Bcl‐2) was down‐regulated in NsSOD overexpressed cells. Taken together, the results indicated that the protein NsSOD might be involved in apoptosis regulation. This study may lay the foundations for further studies on the function of NsSOD and promote the understanding of the virulence factors and the pathogenic mechanisms of N. seriolae .